Comparison of the species composition and distribution of Ichthyoplankton in the Bolusao and Poblacion rivers of Lawaan, Eastern Samar, Philippines. - Pajares, Rackelle Beanne T. (Rackelle Beanne T. Pajares, 2018)
The Bolusao and Poblacion Rivers are important fishing sites in Lawaan, Eastern Samar, Philippines but are currently being threatened by malpractices in the fishing industry. An assessment is imperative in order to establish a baseline and guide the municipality in their resource programs particularly in conserving these rivers. Assessing the species composition and distribution of ichthyoplankton is a relatively inexpensive method that can give a clearer picture on the spatiotemporal distribution of ichthyoplankton. Thus, this study sought to compare the species composition and distribution of ichthyoplankton in the Poblacion and Bolusao Rivers of Lawaan, E. Samar and to determine and compare the influence of environmental variables on the abundance of ichthyoplankton in both rivers. Collection was done from October to November, 2017 and January to February, 2018 using plankton nets (20 um mesh size) through vertical towing. A total of 58 eggs and 4 larvae were collected from the Poblacion River and 55 eggs were from Bolusao River. Scatophagus argus was the dominant species in both rivers. This study showed that both Poblacion and Bolusao Rivers are indeed being utilized as sites for fish spawning and nursery areas but no pattern has been confirmed on the distribution of eggs and larvae along the rivers. The results of this study suggest that Bolusao River is less diverse than Poblacion River in terms of ichthyoplankton composition but this is inconclusive due to the limitation in sampling frequency and the period covered. A more extensive sampling for at least a year is thus recommended for more conclusive results. Environmental variables such as temperature, pH, salinity, water current, depth, and width were found to be correlated to the presence of S. argus eggs in both rivers indicating that spawning for this species may be affected by these parameters.